COMPARATIVE ASSESSMENT OF IN VITRO ANTIMICROBIAL ACTIVITY OF CURCUMA CAESIA ROXB. AND CURCUMA AMADA ROXB - Kaur, Randeep; Kaur, Barinderjit; Suttee, Ashish; Kalsi, Vandna (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the present study was to compare the in vitro antimicrobial activity of Curcuma caesia Roxb. and Curcuma amada Roxb. family Zingiberaceae. Both plants have been used traditionally for curing a number of diseases and ailments. The plants have been specifically used in skin problems and inflammatory conditions. Methods: Each plant material was extracted with dichloromethane (DCM) and ethanol. All extracts were subjected to preliminary phytochemical screening. The antibacterial activity of the extracts was tested against two Gram-positive (Staphylococcus aureus, Streptococcus pyogenes), and two Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa) using the cup-plate method. The standard drug used was ofloxacin (0.2 ml) at a concentration of 5 mg/ml. The antifungal activity was tested against Aspergillus fumigatus, and Candida albicans using the cup-plate method and clotrimazole (10 mg/ml) was taken as standard reference. Results: Phytochemical screening performed on the extracts has shown the presence of various constituents such as glycosides, carbohydrates, saponins, phytosterols, resins, flavonoids, and diterpenoids. On comparing both species, C. amada was found to be stronger growth inhibitor against both Gram-positive and Gram-negative strains. C. caesia ethanol extract at a dose of 200 mg/ml was most effective and C. amada DCM extract 100 mg/ml was least effective in case of antifungal activity against C. albicans. In case of A. fumigatus, C. caesia DCM extract 100 mg/ml was least effective and C. caesia ethanol extract 200 mg/ml was most effective. Conclusion: The present study provides the information on phytochemical screening and antimicrobial activities of extracts prepared from two plants of family Zingiberaceae, i.e., C. caesia Roxb. and C. amada Roxb.